Molecular Evaluation of Interleukin-8, Interleukin-27, and Vascular Endothelial Growth Factor Expression in Prostate Cancer Patients - Saber, Jutyar I.; Fatah, Hiwa R.; Qadir, Fikry A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
Globally, prostate cancer (PCa) is becoming more prevalent and lethal. The progression of PCa is linked to both inflammation and angiogenesis. Pro-inflammatory cytokines, interleukin (IL)-8) and vascular endothelial growth factor (VEGF), promote inflammation, angiogenesis, and PCa progression. On the other hand, IL-27 (IL-27) has antitumor effects, modulates immune system activity, and thus serves as a suppressor of tumor growth. In the Kurdistan Region of Iraq, there is limited evidence linking these cytokines and their gene polymorphisms to PCa. This case–control study included 50 PCa patients and 30 age-matched healthy controls. Serum levels of these three cytokines were evaluated by enzyme-linked immunosorbent assay, whereas PCR and Sanger sequencing were used to find polymorphisms in IL-8 (rs4073, rs2227306), IL-27 (rs153109), and VEGF (rs2010963) in formalin-fixed paraffinembedded tissue DNA. GeneMANIA was used to assess gene-gene interaction networks. Statistical analyses were performed using Mann–Whitney U tests. Patients with PCa showed elevated IL-8 and VEGF levels and reduced IL-27 levels compared to controls (p < 0.05). Multiple single-nucleotide polymorphisms were found in all target genes, several of which were new to the GenBank. Gene-network analysis revealed that these three cytokines are involved in shared inflammatory, immunomodulatory, and angiogenic pathways. This study shows that altered serum levels and gene polymorphisms of these three cytokines may be biomarkers for PCa diagnosis and progression. It underlines the molecular interplay between inflammatory and angiogenic mediators and supports further cytokine-based diagnostic and therapeutic research.